2011
DOI: 10.1063/1.3555612
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial properties and morphologies of graphene-graphane composite sheets

Abstract: The interfaces between graphene and graphane play an important role in developing graphene-graphane-based electronic devices. We identify three most common types of graphane-graphene interface, and perform atomistic simulations to determine three key parameters that characterize the interface structural properties: mismatch strain, tilt angle, and interfacial stress. Further through atomistic simulations, we find that the composite sheets can develop complex morphologies, such as ripples, warps and wedges. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…13,24 Meanwhile, interfacial strain due to partial hydrogenation can affect the morphologies of HGSs. 25 It is predicted such interfacial strain would also have an effect on their thermal properties. Therefore, this study aims to understand the effect of the hydrogenation style and hydrogen coverage on the morphology and k of HGSs via molecular dynamics (MD) simulations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13,24 Meanwhile, interfacial strain due to partial hydrogenation can affect the morphologies of HGSs. 25 It is predicted such interfacial strain would also have an effect on their thermal properties. Therefore, this study aims to understand the effect of the hydrogenation style and hydrogen coverage on the morphology and k of HGSs via molecular dynamics (MD) simulations.…”
mentioning
confidence: 99%
“…Due to hydrogenation, it is found that the lattice parameter of the GA, GO, and RGO sheets is increased by around 5%, which is in good agreement with previous studies. 25,33 Hence, the hydrogenation induces interfacial strain between GA (GO/RGO) and GE strips, leading to the warping of the HGSs, a phenomenon similar to the warping of pure GE sheets induced by their compressive edge stress. [34][35][36] Mechanical and physical properties of a GE sheet strongly depend on its structure, particularly its morphology.…”
mentioning
confidence: 99%
“…The bond length and lattice constant (the second-nearest-neighbor distance) of GE are 1.42 and 2.46 Å, respectively. Due to hydrogenation, it is found that the lattice parameter of the GA, GO and RGO sheets are increased by around 5%, which is in good agreements with previous studies [100,106]. Hence, the hydrogenation induces interfacial strain between GA (GO/RGO) and GE strips, leading to the warping of the HGSs, a phenomenon similar to the warping of pure GE sheets induced by their compressive edge stress [107,108].…”
Section: Morphologysupporting
confidence: 88%
“…On the other hand, external elastic strain applied to GE-based materials has been found to alter their thermal properties by changing their morphologies [66,99]. Meanwhile, interfacial strain due to partial hydrogenation can affect the morphologies of HGSs [100]. It is predicted such interfacial strain would also have an effect on their thermal properties.…”
Section: Ge Hydrogenationmentioning
confidence: 99%
“…We also show that with a small perturbation at the edge is possible to lift the degeneracy between interfaces, allowing a single-interface conduction. The electronic structure simulations were performed within the density functional theory.As in graphane [22], a completely hydrogenated graphene, we can built a germanene nanoroad by removing the hydrogen atoms [23][24][25][26][27] in a desired pattern by, for example, hydrogen dissociation via plasma etching. This germanene structure inside germanane is a non-trivial topological insulator embedded in a trivial insulator and from the bulk-edge correspondence, gapless topological edge states should appear on this lineinterface region.…”
mentioning
confidence: 99%